COVID-19 in Pluralea Interactions: A Case Study in Santo Tomé (Corrientes, Argentina) - Mastrangelo, Andrea Veronica (2023)
This paper is an ethnographic case study of COVID-19 emergence in Santo Tomé (South America, NE Argentina, ≂25,000 inhabitants). Based on interviews with healthcare personnel, we describe local containment and prevention policies in a context of national lockdown measures. We reconstruct a tree diagram of infections, index cases and close contacts that spread infection locally. In parallel, fieldwork in a sample of impoverished subsistence agricultures and fishermen allows us to describe drought and fresh food production decline during confinement as convergent ecocrises (pluralea interactions) with the SARS-CoV-2 outbreak. The core idea of the article, which emerged from ethnographic fieldwork evidence, is that in the context of climate change, the sudden onset of an infectious disease interacts with convergent ecocrises.